Low Glomerular Filtration Rate, Recurrent Stroke Risk and Effect of Renin Angiotensin System Modulation - Ovbiagele, Bruce (2013)
BACKGROUND AND PURPOSE: To investigate the association of low glomerular filtration rate {eGFR} < 60 mL/min with recurrent stroke risk, and evaluate whether add-on renin-angiotensin system (RAS) modulator therapy is associated with lower recurrent stroke risk in patients with low eGFR. METHODS: We analyzed the database of a multicenter trial involving 18,666 patients with recent ischemic stroke followed for 2.5 years. Primary outcome was time to first recurrent stroke. Independent associations of low eGFR with outcome in the entire cohort; and add-on telmisartan treatment with outcome among those with low eGFR were evaluated. RESULTS: Low eGFR was observed in 3630 (20.1 %) patients. Low eGFR patients were older, more likely female, with a known history of hypertension. In unadjusted analyses, low eGFR patients were more likely to experience a recurrent stroke (HR 1.34, 95% CI: 1.20 – 1.49). After adjusting for confounders, low eGFR was still associated with recurrent stroke, but to a lesser extent (HR 1.16, 95% CI: 1.04 – 1.31). Telmisartan treatment among low eGFR patients was not independently associated with recurrent stroke (HR 1.08, 95% CI: 0.89 – 1.31). CONCLUSIONS: Low eGFR is independently associated with a higher risk of recurrent stroke, but short-term add-on telmisartan therapy does not seem to mitigate this risk. CLINICAL TRIAL REGISTRATION-URL: http://www.clinicaltrials.gov. Unique identifier: NCT00153062